The Role of Brand Awareness, Advertising Effectiveness, and Pricing Strategies on Market Share of Green Products - Abidin, Zainal; Kristian Panjaitan, Feliks Anggia Binsar (International Journal of Business, Law, and Education, 2024)
This study investigates the impact of brand awareness, advertising effectiveness, and pricing strategies on the market share of green products. Using a sample of 500 respondents and employing multiple regression analysis, the findings reveal that all three factors significantly and positively influence market share. Brand awareness emerged as the most critical factor, followed by advertising effectiveness and pricing strategies. The study highlights the importance of strategic marketing efforts in promoting green products and provides practical implications for marketers. Companies are advised to invest in branding, create effective advertising campaigns, and adopt competitive pricing strategies to increase their market share. This research contributes to the literature on green marketing and offers insights into the drivers of market success for sustainable products.